Contemplating the Christ Child for Imagining a Christian Educational Vision that Liberates Children - Pang, Alfred (Lumen et Vita, 2016)
As theological educators, how are we responding to the death and suffering of the world’s children caused by human agency? Are we moved beyond anguish to be indignant at the various forms of injustice committed against children? To what extent has theology made room for children as its subject in today’s troubled world? This paper considers how the Christ Child, as a focus of contemplation, can be formative in shaping our theological, moral, and pedagogical imagination for children’s liberation. It retrieves and interprets the significance of the Christ Child in John Baptist De La Salle’s Explanation of the Method of Interior Prayer and his Meditations, arguing for their contemporary relevance in nourishing a Christian educational vision that makes room for the rights of children to be taken seriously.